PENGARUH ASSET GROWTH, ARUS KAS OPERASI, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGANPERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2017 - FX SRI WARDAYA (STIE St. Pignatelli Surakarta, 2020)
This research aims to test the influence of variable asset growth, operating cash flows, institutional ownership and the size of the company against the financial performance of the company. The object of the research is 143 manufacturing companies listed on the Indonesia stock exchange years 2014-2017. Sampling in research using the method of purposive sampling. The sample used is 60 companies. The source of the data in this study are accessed directly from www.idx.co.id. The methodology used to see the influence between the dependent and independent variables in this study was conducted with multiple linear analysis (multiple linear regression). The results showed that the variable asset growth, institutional ownership and the size of the company's positive effect on performance of financial firms with the significance of 0.003, 0.030 and 0.000< 0,05 while operating cash flow is not effect on the financial performance of perusahaa with a level of significance of 0.228>0,05. Based on the testing coefficients of determination, retrieved the value R Square (R2) by 0.286. Thus the variable asset growth, operating cash flow, the company's institutional ownership and sizes affect the company's financial performance amounted to 28,6% 71,4%, while influenced by other factors. In conclusion, the variable asset growth, institutional ownership and size of companies significant effect, while operating cash flow was not significant effect against the financial performance of the company